Tingkat Pengetahuan Berhubungan dengan Usaha Mencari Bantuan Terkait Kegawatdaruratan Medis di Kota Yogyakarta : Knowledge Level Associated with Help Seeking Related to Medical Emergencies in Yogyakarta City - Lukman Nulhakim Abdul Kader; Teguh Santoso; Erika Nurwidiyanti (NERS Jurnal Keperawatan, 2021)
Emergencies are circumstances that require immediate action or require first aid. The most common emergency is a traffic accident which can cause injuries. The death toll from traffic accidents is 30,000 people per year and the morbidity is 20,000 people per year. Efforts are being made to reduce the number of mortality and morbidity that is issued by PSC 119 emergency medical services. This study aims to analyse the correlation between knowledge level and effort to seek help related to an medical emergency. This is a descriptive correlation with a cross-sectional approach. The number of respondents was 348 people using incidental sampling. Data were collected using a questionnaire level of knowledge and efforts to seek help. In addition, Kendall's tau test is used to determine the relationship between variables. The result showed the level of knowledge of 250 respondents (71.8%) was categorized as very good, 79 respondents (22.7%) have a good category, 8 respondents (2.3%) have a sufficient category, and 11 respondents (3.2%) in the poor category. The efforts to seek help by respondents were categorized as very good 72 respondents (20.7%), good category are 67 respondents (19.3), sufficient category are 86 people (24.7%), less category totaled 48 respondents (13.8%), and 75 respondents (21.5 %) is in the failed category. The relationship between variables is significant with value = 0.000 (p = 0.01). However, the correlation coefficient value is 0.180. There is a significant relationship between the level of knowledge and efforts to seek help but have a weak correlation.